Effects of silicate and carbonate substitution on the properties of hydroxyapatite prepared by aqueous co-precipitation method. (15th December 2015) - Bang, L.T.; Ramesh, S.; Purbolaksono, J.; Ching, Y.C.; Long, B.D.; Chandran, Hari; Ramesh, S.; Othman, R.
Abstract: This research was conducted to investigate the effects of silicate and carbonate substitutions in hydroxyapatite (HA) on phase retention, physical properties, and in vitro biological response. A wet chemical method was employed to synthesize silicate-substituted HA (Si–HA) and carbonate-substituted HA (CHA). It was shown that the presence of silicate and carbonate ions in the HA lattice increases the specific surface area and Ca/P molar ratio. In addition, the substitution also resulted in a reduction in the crystallinity of the HA powder and promoted better bioactivity of the sintered body. This was confirmed through in vitro cell culture experiment which revealed that the osteoblast cells adhered well on the surface of the ceramic and that ionic-substituted HA exhibited better cell performance than the control HA. Graphical abstract: Highlights: Hydroxyapatite (HA) with ionic substitution of carbonate and silicate was prepared. Substitution causes lattice disorder and suppresses grain coarsening of HA. Ionic-substituted HA results in better dissolution compared with un-substituted HA. The substitution of SiO4 4 − and CO3 2 − ions enhances biological response.